1993
DOI: 10.1002/bio.1170080504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salmeterol on polymorphonuclear leukocyte (PMNL) chemiluminescence In Vitro

Abstract: Although beta-agonists remain an important aspect of the treatment of asthma, their role has recently been questioned. Salmeterol has recently been developed as a beta-agonist with prolonged bronchodilator action. Using lucigenin-enhanced chemiluminescence, we have shown that salmeterol inhibits this aspect of phagocyte function in vitro in a concentration-dependent manner. However, salmeterol differs from classical beta 2-agonists in that at concentrations between 10(-5) and 10(-3) mol/L, its effects on phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…This contention is supported by observations that the inhibitory effects of salmeterol on oxidant production by activated neutrophils were insensitive to propranolol and almost completely eliminated by washing the cells. These observations confirm previous studies in which salmeterol has been reported to inhibit oxidant generation by FMLP-and opsonized zymosan-activated neutrophils by undefined, P2adrenoceptor-independent mechanisms (Ramage et al, 1993;Vardey et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This contention is supported by observations that the inhibitory effects of salmeterol on oxidant production by activated neutrophils were insensitive to propranolol and almost completely eliminated by washing the cells. These observations confirm previous studies in which salmeterol has been reported to inhibit oxidant generation by FMLP-and opsonized zymosan-activated neutrophils by undefined, P2adrenoceptor-independent mechanisms (Ramage et al, 1993;Vardey et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…This contention is supported by observations that the inhibitory effects of salmeterol on oxidant production by activated neutrophils were insensitive to propranolol and almost completely eliminated by washing the cells. These observations confirm previous studies in which salmeterol has been reported to inhibit oxidant generation by FMLP-and opsonized zymosan-activated neutrophils by undefined, P2-adrenoceptor-independent mechanisms (Ramage et al, 1993;Vardey et al, 1994). The inhibitory effects of salmeterol on neutrophil superoxide generation were dose-related and observed with all four stimuli of membrane-associated oxidative metabolism, the intensity of their pro-oxidative interactions with these cells being an apparent determinant of sensitivity to salmeterol.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While there is very little evidence that these agents modify disease in a clinical setting [1], conven tional short-acting P-agonists do have anti-inflammatory ef fects in vitro [2,3], Consequently it seemed possible that recently produced long-acting P-agonists such as salmete rol might have disease-modifying activity. We have demon strated that salmeterol alters phagocyte function in vitro [4], and others have shown that salmeterol inhibits both aller gen-induced mediator release and inflammatory cell migra tion [5,6]. However, there is only one report containing re sults suggestive of a clinical anti-inflammatory effect [7].…”
Section: Introductionmentioning
confidence: 99%